The Architecture and Key Technologies of the Internet of Things with Integration of Heaven and Earth and Multi Services - Xiao WEI; Jing ZHANG; Ziao QUAN; Yinuo GUO; Xu FENG (天地一体化信息网络)
In view of the requirements of the new internet of things , such as multi diff erentiated service, wide area high-capacity access, low power consumption and low cost, the architecture design, technology research and system construction of the new generation satellite internet of things are in the stage of extensive research and experiment.In this context, based on the analyzed of the research status and requirements, an internet of things architecture integrating heaven and earth was proposed.Then, the research on technologies such as multi service integration air interface transmission, communication and positioning integration, and intelligent edge computing were deeply studied.A multi-scene space based internet of things solution for low latitude areas was put forwared, which provided a reference for the future development of space-based internet of things technology and system construction.